2018
DOI: 10.1371/journal.pone.0192881
|View full text |Cite
|
Sign up to set email alerts
|

The ARID1A, p53 and ß-Catenin statuses are strong prognosticators in clear cell and endometrioid carcinoma of the ovary and the endometrium

Abstract: AimThe objective of this study was to evaluate the prognostic value of ARID1A, p53, p21, p16 and ß-Catenin in endometrioid and clear cell ovarian and endometrial carcinomas.Materials and methods97 tumors were available for analysis of ARID1A, p53, p21, p16 and ß-Catenin with the techniques of tissue microarray and immunohistochemistry. 32 were ovarian carcinomas and 65 were endometrial carcinomas.ResultsEndometrioid ovarian carcinomas showed negative staining for ARID1A (a) and p21 (b), aberrant expression of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
31
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 44 publications
(40 citation statements)
references
References 57 publications
5
31
3
Order By: Relevance
“…In our research group, the same collective of patients has already been worked with. In the corresponding papers, the expression of ARID1A, β-Catenin p16, p21, p53, and the steroid receptors ERα, ERβ, PRα, and PRβ has been described [ 29 , 30 ]. In these studies, tumor material of the exact same patients has been immunohistochemically stained for the above-mentioned proteins and respective expression analyzed.…”
Section: Resultsmentioning
confidence: 99%
“…In our research group, the same collective of patients has already been worked with. In the corresponding papers, the expression of ARID1A, β-Catenin p16, p21, p53, and the steroid receptors ERα, ERβ, PRα, and PRβ has been described [ 29 , 30 ]. In these studies, tumor material of the exact same patients has been immunohistochemically stained for the above-mentioned proteins and respective expression analyzed.…”
Section: Resultsmentioning
confidence: 99%
“…Heckel et al found that the expression of ARID1A and absent nuclear β-Catenin staining were positive prognosticators in endometrioid and clear-cell carcinoma of the uterus and the ovaries (Heckl et al 2018 ). We detected a positive correlation of SIRT1 expression in the examined entities with both proteins, ARID1A and β-Catenin.…”
Section: Discussionmentioning
confidence: 99%
“…The membrane was blocked at room temperature in a solution of 3% nonfat dry milk in PBS and 0.1% Tween-20 and then rinsed in PBS/0.1% Tween-20. Blots were incubated with diluted solutions of anti-P53 (1:1000, Cell Signaling Tech, Danvers, MA, USA) [ 15 ] and anti-HNF-1β (1:500, GeneTex) [ 16 , 17 ] antibodies (previously reported expression in CCC) and treated with 1:5000 diluted anti-rabbit immunoglobulin G horseradish peroxidase (HRP) for staining (Amersham GE, Taipei, Taiwan). GAPDH proteins (1: 200, GeneTex) were used as internal controls.…”
Section: Methodsmentioning
confidence: 99%